2004
DOI: 10.1177/147323000403200608
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Risk Factors in Patients with Obstructive Jaundice

Abstract: Clinical and laboratory parameters that may affect post-operative mortality and morbidity were studied in 215 patients operated on for obstructive jaundice. The cause of the bile duct obstruction was benign disease in 56.7% of patients and malignant disease in 43.3%. Overall postoperative mortality and morbidity rates were 21.9% and 33.5%, respectively. Eight risk factors were shown to be associated with increased mortality: age > 70 years; malignancy; leucocytosis > 15 000 cells/microl and fever > 38.5 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
0
17
1
Order By: Relevance
“…sepsis, coagulopathy, hepatic coma and renal failure) have been reported in literature to be associated with high mortality rate in these patients (Hussain &Fatima, 2000;Pitiakoudis et al, 2004;Uslu et al, 2007;Moghimi et al, 2008;Chalya et al, 2011). Our mortality rate of 20.3% was higher that reported by others (Moghimi et al;Chalya et al, 2011).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…sepsis, coagulopathy, hepatic coma and renal failure) have been reported in literature to be associated with high mortality rate in these patients (Hussain &Fatima, 2000;Pitiakoudis et al, 2004;Uslu et al, 2007;Moghimi et al, 2008;Chalya et al, 2011). Our mortality rate of 20.3% was higher that reported by others (Moghimi et al;Chalya et al, 2011).…”
Section: Discussioncontrasting
confidence: 54%
“…The mortality and morbidity of biliary obstruction are dependent on the cause of the obstruction, and the assessment of any factors which influence the morbidity and mortality in patients with obstructive jaundice in each society is necessary (Moghimi et al, 2008;Pitiakoudis et al, 2004). Understanding factors responsible for increased morbidity and mortality in these patients will better guide appropriate management and lead to improved survival (Buckwate, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…The mortality and morbidity of biliary obstruction are dependent on the cause of the obstruction, and the assessment of any factors which influence the morbidity and mortality in patients with obstructive jaundice in each society is necessary [6,15]. It has been reported that obstructive jaundice continues to be associated with significant morbidity and mortality despite recent advances both in preoperative diagnosis and postoperative care [15-17]. Understanding factors responsible for increased morbidity and mortality in these patients will better guide appropriate management and lead to improved survival [17].…”
Section: Introductionmentioning
confidence: 99%
“…Delay in presentation and treatment can lead to significant morbidity and mortality due to secondary infections causing cholangitis, liver abscess and systemic effect like malnutrition, weight loss, decreased immunity and renal insufficiency. [16] In our study too, benign causes were commoner, but post cholecystectomy biliary stricture was commonest as opposed to stone disease, seen in only one. In a study of 116 patients by Chalya et al, [14] higher number of patients (58.6%) had association with malignant etiology but choledocholithiasis was the commonest (62.5%) cause among benign (62.5%) and carcinoma of the head of pancreas (64.7%) among the malignant causes similar to our study.…”
Section: Discussionmentioning
confidence: 93%